2011
DOI: 10.1101/gr.124115.111
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and assessment of conserved Pax6 target genes and enhancers

Abstract: The characterization of transcriptional networks (TNs) is essential for understanding complex biological phenomena such as development, disease, and evolution. In this study, we have designed and implemented a procedure that combines in silico target screens with zebrafish and mouse validation, in order to identify cis-elements and genes directly regulated by Pax6. We chose Pax6 as the paradigm because of its crucial roles in organogenesis and human disease. We identified over 600 putative Pax6 binding sites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 76 publications
1
46
0
Order By: Relevance
“…Nuclear protein gene Mab21l1 (Yamada et al, 2003) and the secreted frizzled-related protein gene Sfrp2 (Wawersik et al, 1999) are also downregulated in the Sey mutant. In a zebrafish study of pax6 targets (Coutinho et al, 2011) a number of genes are downregulated upon morpholino antisense oligonucleotide treatment of embryos and studies on specific differentiated tissues in the mouse, e.g. the lens, provide a more global analysis of later Pax6 targets (Wolf et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear protein gene Mab21l1 (Yamada et al, 2003) and the secreted frizzled-related protein gene Sfrp2 (Wawersik et al, 1999) are also downregulated in the Sey mutant. In a zebrafish study of pax6 targets (Coutinho et al, 2011) a number of genes are downregulated upon morpholino antisense oligonucleotide treatment of embryos and studies on specific differentiated tissues in the mouse, e.g. the lens, provide a more global analysis of later Pax6 targets (Wolf et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…32 Interestingly, morpholino-induced knockdown of pax6a or simultaneous knockdown of pax6a and pax6b results in a similar but more severe phenotype; morphants present with reduced body size and neural tube girth, morphologically abnormal brain development, and microphthalmia. 33 TALENs-mediated knockdown of pax6a and pax6b simultaneously, by targeting conserved sequences between these paralogs, resulted in eye phenotypes including microphthalmia, closely recapitulating the ocular morphant phenotype described. 34 The strategy employed not only confirms the efficiency of TALENsmediated gene disruption, but also emphasises the ability to induce bi-allelic and paralogous genome editing, which is important when investigating genes that are duplicated in the zebrafish genome.…”
Section: Pde6cmentioning
confidence: 99%
“…To determine whether Pax6 binds this enhancer, ChIP-qPCR was performed on caudal neural tube tissues from E11.5 embryos using an anti-Pax6 antibody (Coutinho et al, 2011) and primers that span the identified potential Pax6 binding sites. This region was found to be significantly enriched compared with a negative control region (Kirrel2) (Borromeo et al, 2014) (supplementary material Fig.…”
Section: Cloning and Expression Of Xenopus Chicken And Amphioxus Prdmentioning
confidence: 99%